Optimizing Teacher Performance: An Empirical Analysis of School Climate and Academic Supervision in Primary Education - Adriantoni Adriantoni; Efrita Roni; Menaga Vesudevan; Wina Apriana (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This study aims to analyze the influence of school climate and academic supervision on teacher performance, both partially and simultaneously, in elementary schools. This research employed a quantitative approach with a population of 71 elementary school teachers. Data were collected via questionnaires and analyzed using simple and multiple linear regression in SPSS version 26. The findings reveal that school climate has a significant effect on teacher performance, accounting for 14.8% of its variation. Academic supervision also has a significant influence, contributing 11.6%. Furthermore, school climate and academic supervision simultaneously affect teacher performance by 31.8%, while the remaining 68.2% is influenced by other factors not examined in this study. Descriptive analysis shows that the implementation of school climate reached 87.88%, categorized as good, and academic supervision reached 86.48%, also categorized as good. These findings indicate that a supportive school climate and effective academic supervision are essential factors in improving teacher performance. The study provides empirical evidence to help school leaders and educational stakeholders strengthen school management practices and professional development programs.